2. Achieving Harmony Through Music: A Comparison Between Ancient Greek and Chinese Thought - Marisi Rossella (Sciendo, 2020)
Ancient Greek and Chinese philosophers held music as a fundamental component of education and deemed it effective in guiding students at gaining harmony within themselves and with one another. A quality music education was thus considered relevant in the Bildung of individuals, the preservation of the state, and the maintenance of harmony between heaven and earth. This study makes a comparison between the thought of Plato and his Greek predecessors on one side, and the one of Confucianism on the other, identifying fascinating similarities which offer a source of inspiration to modern educators.